Pengaruh Literasi Keuangan Dan Financial Self- Efficacy Terhadap Risky Credit Behavior Dalam Penggunaan Paylater Pada Mahasiswa Generasi Z Di Stbm Dua Sudara Bitung - Christiany Shyntia Tombokan; Stephanie Mervin Tooy; Oktaviani Ramenusa; Christophel Patrik N. Sapan (Jurnal Economic Resource, 2026)
This study aims to analyze the influence of financial literacy and financial self- efficacy on risky credit behavior in the use of paylater services among Generation Z students at STBM Dua Sudara Bitung. The rapid growth of digital financial services, particularly the Buy Now Pay Later (BNPL) feature, provides easier access to credit, which may encourage risky credit behavior if not supported by adequate financial knowledge and self-control. Research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z students at STBM Dua Sudara Bitung. Data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). Results indicate that financial literacy has a negative and significant effect on risky credit behavior, meaning that higher levels of financial literacy reduce the tendency toward risky credit use. Financial self-efficacy also has a negative and significant effect on risky credit behavior, indicating that individuals’ confidence in managing their finances can minimize irresponsible credit usage. Simultaneously, financial literacy and financial self-efficacy significantly influence risky credit behavior. Findings highlight the importance of improving financial literacy and strengthening financial self-confidence to promote more responsible digital credit usage among university students.